Spatiotemporal variations in trawling intensity in the German Baltic Sea Basins based on bathymetric data - Peter Feldens; Inken Schulze; Jacob Geersen; Elisabeth Seidel; Svenja Papenmeier; Aicha Naumann; Daniel Oesterwind; Mischa Schönke (Anthropocene, 2026)

Oceanographic parameters associated with spatial occurrence of cephalopods in standardized demersal fishing trawls in the NE Atlantic - Daniel Oesterwind; Anne Marie Power; Esther Abad; Gregoire Certain; Nikolaos Fotiadis; Alexey Golikov; Ángel F. González; Vladimir Laptikhovsky; Silvia S. Monteiro; Carlos Montero-Castaño; Ana Moreno; Hassan Moustahfid; et al. (Marine Biology, 2026)
In this work, the environmental occurrence ranges of different European cephalopod species are described for the whole NE Atlantic shelf including the greater North Sea and Baltic Sea. This is done based on the environmental parameters collected in-situ during surveys that caught commercially important cephalopod species (1990–2022). Results are supplemented and compared with information available in the published literature and are discussed in relation to available habitat across the range, survey design, etc., and, in particular, which species are most likely to be affected by climate change. Our analyses illustrate that Loligo forbesii occupies a broader depth range than Loligo vulgaris and Alloteuthis spp. Because L. forbesii occurs further offshore and at greater depths, this species is likely more resilient to warming than the other loliginids in our study. Octopus vulgaris is documented in areas close to the coast with a more southerly distribution, whereas Eledone cirrhosa occurs further north and further away from the coast. Eledone cirrhosa occurs at lower temperatures and has a much broader depth range, which may provide resilience against warming. By contrast, both ommastrephid squid species ( Illex coindetii and Todaropsis eblanae ) showed a very similar tolerance to the three environmental variables (salinity, temperature, depth). This information should contribute to future species distribution modelling by allowing validation of realistic results against each species’ range, habitat requirements, and environmental ranges, while appreciating the data limitations caused by the timing and gear used in the survey cruises that supply occurrence and density data.

Value and Volatility of Squid as a Fisheries Resource in the North Sea and Adjacent Waters—Starting Point for a Sustainable Management - Erik Sulanke; Ralf Döring; Daniel Oesterwind (Fisheries Management and Ecology, 2026)

Classification of European Illex coindetii and Loligo forbesii Squid Stocks by Trace Element Analysis of Statoliths - Bianca T. C. Bobowski; Anne Marie Power; Finlay Burns; Pierluigi Carbonara; Danila Cuccu; Maria Cristina Follesa; Klaus Peter Jochum; Ana Moreno; Inna M. Sokolova; Maria Valls; Daniel Oesterwind (Fisheries Management and Ecology, 2026)
We investigated whether statolith microchemistry analysis could classify ommastrephid and loliginid squid species into fishery stocks. Statolith nucleus (early life stage) and edge (life stage at time before catch) of Illex coindetii (Verany, 1839) and Loligo forbesii (Steenstrup, 1856) from various areas of the North East Atlantic Ocean and Mediterranean Sea during 2021–2022 were analysed using laser ablation ICP‐MS to measure values of 11 trace elements (Na, Mg, Mn, Fe Co, Cu, Zn, Sr., Ba, Pb and U) next to calcium. Four stocks were categorised for I. coindetii and five stocks for L. forbesii amongst sample areas. Common hatching areas and migration into distinct fishing regions were also identified. Our results provide substantial information to sustainably manage fisheries for both species in European waters by providing stock definitions, spawning periods and migration patterns.

First description of the emergence of targeted squid fisheries in the German North Sea demersal trawl fleet - Erik Sulanke; Ralf Döring; Daniel Oesterwind (Regional Studies in Marine Science, 2026)

The reproductive ecology of Loligo squids (Cephalopoda: Myopsida) in Lusitanian zoogeographical province - Vladimir Laptikhovsky; Ana Moreno; Daniel Oesterwind; Catalina Perales-Raya; Graham Pierce; Jean-Paul Robin; Ignacio Sobrino; Maria Valls; Roger Villanueva; Athena Allen; Esther Abad; Giambattista Bello; et al. (Regional Studies in Marine Science, 2025)

Improving species distribution models for climate change studies: ecological plausibility and performance metrics - Dario Fiorentino; Ismael Núñez-Riboni; Maria E. Pierce; Daniel Oesterwind; Anna Akimova (Ecological Modelling, 2025)

Trophic ecology of squids in the Benguela Upwelling System elucidated by combining stomach content, stable isotope and fatty acid analyses - Kira Izabela Kremer; Wilhelm Hagen; Daniel Oesterwind; Sabrina Duncan; Maya Bode-Dalby; Sabrina Dorschner; Tim Dudeck; Anne F. Sell (Marine Biology, 2025)
Squids occur worldwide in marine ecosystems and play a major role in pelagic food webs by connecting lower and higher trophic levels. Their high feeding intensities and pronounced diel vertical migrations make squids important components of nutrient cycles in marine ecosystems. This study assessed the trophic position and nutritional ecology of a squid species assemblage in the Benguela Upwelling System (BUS) by combining stomach content, stable isotope and fatty acid trophic marker analyses. Samples were collected in the northern (nBUS) and southern (sBUS) BUS in austral spring 2021. A total of 20 squid species from eleven families were identified. Stomach content analyses showed that squid species preyed on a variety of organisms ranging from crustaceans to lanternfishes (Myctophidae) and flying squids (Ommastrephidae). Stable isotope analyses revealed significant differences in δ 15 N values of small squids (dorsal mantle length < 10 cm) between the two subsystems, but none in those of large squids (dorsal mantle length > 10 cm). Trophic levels ranged from 2.2 to 5.0. Isotopic niche width was widest in the families Ommastrephidae and Cranchiidae. Principal component analyses of fatty acid compositions displayed distinct clusters separating squid families and different prey taxa. This study shows that nBUS and sBUS squids exploit a large variety of pelagic prey organisms and that trophic differences are primarily dependent on squid species and size. The results emphasize the squids’ importance as interlinking element in pelagic food webs and their key function in energy transfer between epi- and mesopelagic layers.

Disentangling the potential effects of four non-indigenous species on commercially and recreationally used fish stocks in the Baltic Sea—a review - Daniel Oesterwind; Valerio Bartolino; Jane W. Behrens; Marten Erlandsson; Ann-Britt Florin; Christina Henseler; Magdalena Jakubowska-Lehrmann; Cornelia Jaspers; Maiju Lehtiniemi; Rahmat Naddafi; Katarzyna Nadolna-Ałtyn; Ivars Putnis; et al. (Biological Invasions, 2025)
Non-indigenous species (NIS) are on a rise globally. They can pose strong impacts on ecosystems in their non-native range and can therefore be a serious threat to biodiversity. Here, we compile the existing information available regarding the extent to which commercially and recreationally used fish stocks (exploited fish species) are affected by NIS. To do so, we conducted a literature review to summarize the known and presumed impacts of four case study NIS with already known strong effects on the Baltic Sea ecosystem: round goby, Neogobius melanostomus , sea walnut, Mnemiopsis leidyi , mud crab, Rhithropanopeus harrisii , and fishhook water flea, Cercopagis pengoi. We found that round goby, mud crab and fishhook water flea are documented to serve as a new food source for native fish species, while sea walnut and fishhook water flea are supposedly affecting planktivorous fish through resource competition. Round goby is very likely a strong competitor for the benthivore fish community. There are also indications that it feeds on juvenile fish and fish eggs. Generally, our results show that large knowledge gaps exist, while the published impacts on exploited fish species are often solely based on correlations (e.g. decreasing abundances of native species with cooccurring increasing abundances of NIS), regionally restricted studies or expert judgements. In addition, many studies are older and the current population size of the NIS, which is obviously associated with their impact, is unknown. Thus, the majority of described impacts of NIS on commercially and recreationally used fish stocks seems to stem from assumptions. Therefore, more field observations and experimental studies are needed to be able to scientifically evaluate the impact of NIS. Nevertheless, in this review, the available information was summarized, even if they are speculative, and specific knowledge gaps were identified. Moreover, we outline further investigations that are needed to advance our mechanistic understanding of the interactions between NIS and exploited fish species in the Baltic Sea. This knowledge is essential for the sustainable management of aquatic resources and management of NIS of the Baltic Sea.

Fatty acid analyses reveal differences in feeding ecology of North Sea squids that overlap in time and space - Fabian Schäfer; Daniel Oesterwind; Anne F. Sell; Ulrike Kammann (Food Webs, 2024)

Stock discrimination of two European squids ( Illex coindetii , Loligo forbesii ) by statolith shape analysis - Bianca T. C. Bobowski; Anne Marie Power; Finlay Burns; Pierluigi Carbonara; Danila Cuccu; Marilena Donnaloia; Maria Cristina Follesa; Ana Moreno; Inna M. Sokolova; Maria Valls; Daniel Oesterwind (Fisheries Management and Ecology, 2024)
We evaluated the feasibility of classifying ommastrephid and loliginid squid species by statolith shape analysis into fisheries management units or stocks. Statoliths of Illex coindetii (Verany, 1839) and Loligo forbesii (Steenstrup, 1856) were studied from multiple areas of the North East Atlantic and Northern Mediterranean Sea during 2021–2022. I. coindetii and L. forbesii individuals were categorized into multiple stocks across the areas studied. Stocks migrating between fishing areas as well as multiple stocks in the same area, as identified for L. forbesii in this study, need to be considered for sustainable fisheries management.

Identifying fit-for purpose methods for monitoring fish communities - Constanze Hammerl; Christian Möllmann; Daniel Oesterwind (Frontiers in Marine Science, 2024)
Scientific monitoring is a fundamental basis of scientific advice. Among others, monitoring aims at contributing towards understanding the influence of anthropogenic use (e.g. fisheries), the health of a stock and individuum and effectiveness of management and conservation measures (e.g. MPAs). Monitoring of demersal and benthic fish communities is often based on invasive methods like bottom trawling, however in some cases less invasive methods might be available. The need for developing alternative and less invasive monitoring methods is supported by an increasing number of Marine Protected Areas and Windfarms where traditional methods such as trawls cannot be deployed due to conservational or technical and safety reasons. To support the development of new monitoring concepts, we conducted a literature review to identify limits and opportunities of methods that are already available. Furthermore, we present a fit-for purpose guide that can help identifying the appropriate method for individual purposes. We defined eight different methods which were analyzed using four different criteria and listed their advantages and disadvantages. We further apply this guide to monitoring in Marine Protected Areas in the Baltic Sea as a case study, indicating that besides traditional bottom trawling, alternative and less invasive methods could be sufficient for specific research purposes. We therefore, encourage scientists and managers to consider alternative data collection methods to minimize environmental impact of scientific sampling. However, our results also indicate that most of the methods still need further refinement especially regarding sampling design, standardization of methods and comparability with established survey methods.

Trophic ecology and seasonal occurrence of two Red List fish species in the Western Baltic Sea—two of a kind? - Daniel Oesterwind; Linda Köhler; Martin Paar; Christina Henseler; Michael Kriegl; Mayya Gogina; Hendrik Schubert; Pedro Martínez Arbizu (Marine Biodiversity, 2023)
Improving the conservation status and the management of Red List species requires knowledge on the biology and distribution of the organisms as well as an evaluation of the appropriateness of management measures. This study provides information on the trophic ecology and seasonal abundances of two Red List fish species from the Western Baltic Sea, snake blenny Lumpenus lampretaeformis (Walbaum, 1792), classified as “critically endangered” according to the German Red List, and eelpout, Zoarces viviparus (Linnaeus, 1758), classified as “near threatened” based on the HELCOM Red List. Beam trawl surveys were conducted to document abundances of both species in summer and winter in a marine protected area (MPA), where mobile bottom-contacting fishing gears will be excluded in the near future. The MPA is located in the German EEZ (exclusive economic zone) and aims to protect sandbank and reef habitats. Stomach content and stable isotope analyses (nitrogen and carbon) were performed to examine the diet of eelpout and snake blenny. To be able to position the two fish species in the food web, stable isotopes of macrozoobenthos, POM (particulate organic matter) and sand goby ( Pomatoschistus minutus ) were analysed as well. Eelpout and snake blenny were present in the study area in summer and winter, but reached higher abundances in summer. Diet composition overlapped strongly reflected by a similar trophic level, indicating potential food competition of the two species. Prey items were dominated by macrozoobenthos (Mollusca, Annelida, Arthropoda). Our study provides new information on the trophic position and seasonal abundance of the two fish species within an area soon to be placed under protection from mobile bottom-contact fishing. It therefore also provides a baseline to evaluate potential positive repercussions following the exclusion of mobile bottom-contacting fishing gears and might thus help to increase the understanding of fishing impacts on benthic ecosystems contributing to more effective conservation and management measures.

Temporal development of fish communities in brackish lagoons of the Baltic Sea considering the invasion of the non-indigenous round goby (Neogobius melanostomus) - Wolf-Christian Lewin; Malte Dorow; Christina Henseler; Daniel Oesterwind; Marc Simon Weltersbach; Harry V. Strehlow (Regional Studies in Marine Science, 2023)

Stomach content analysis of North Sea cephalopods: often-overlooked predators with direct impact on commercially used fish species? - Daniel Oesterwind; Uwe Piatkowski (Marine Biology, 2023)
The study of marine food web models has increased during the last years, but input data of important groups such as cephalopods are missing sometimes which restricts the quality of the model results. Cephalopods feed on a variety of preys, ranging from small crustaceans to large commercially important fish species. In turn, they are taken by larger invertebrates, fish, cephalopods, marine mammals and seabirds, which emphasizes their important role in various marine food webs. Our study presents stomach content analyses of various cephalopod species from the North Sea and describes their general feeding trends. The results further support the inclusion of cephalopods as predators into food web models to increase our knowledge of the North Sea ecosystem and to improve its management. Our data in combination with observed increasing biomasses of North Sea cephalopods suggest that the impact of cephalopods in the North Sea food web has increased and that large-sized cephalopods have become more important as predators for commercially exploited fish species during recent years.

Trophic redundancy in benthic fish food webs increases with scarcity of prey items, in the Southern Baltic Sea - Camille de la Vega; Martin Paar; Linda Köhler; Christian von Dorrien; Michael Kriegl; Daniel Oesterwind; Hendrik Schubert (Frontiers in Marine Science, 2023)
Bottom trawling is one of the main pressures on benthic ecosystems, directly impacting the targeted species and physically disturbing the seabed and the benthic invertebrate communities, in turn indirectly impacting benthivorous fish and the entire benthic food web structure and functioning. To predict the cascading effect of bottom trawling on benthic and demersal fish communities, it is crucial to understand the trophic interactions between benthic and demersal fish and benthic invertebrates. Here, we assessed the diet of benthic and demersal fish and the structure and functioning of the benthic food web in two areas in the German Baltic Sea, the Fehmarnbelt and the Odra Bank. The Fehmarnbelt benthic invertebrate community is characterized by a high number of species and biomass, contrary to the one on the Odra Bank which is species poor with high individual abundance but low biomass. We used mixing models based on stable isotopes of carbon and nitrogen combined with stomach content analyses to estimate the fish diet at both sites, and we used community-wide trophic indices, derived from stable isotopes to compare the structure and functioning of the fish benthic food webs. We show that fish in the Fehmarnbelt can chose preferential prey items, resulting in higher trophic diversity, contrary to fish on the Odra Bank, which feed on all available prey species, resulting in higher trophic redundancy. We found that the generalist behavior of fish on the Odra Bank is likely the result of scarcity in prey items, the benthic invertebrate community being species poor with high abundance of small individuals. We demonstrate that the differences in structure and functioning of the benthic fish food web between the two sites was mainly driven by differences in the characteristics of the benthic prey communities.

Evidence of phenotypic plasticity in Alloteuthis media (Linnaeus, 1758) from morphological analyses on North Sea specimens and DNA barcoding of the genus Alloteuthis Wülker, 1920 across its latitudinal range - Edel Sheerin; Anne Marie Power; Daniel Oesterwind; David Haak; Esther Abad; Leigh Barnwall; Michael Petroni; Ignacio Sobrino; Julio Valeiras; A. Louise Allcock (Marine Biology, 2023)
Despite being landed in commercial cephalopod fisheries, species of Alloteuthis are not yet well defined, with A. subulata and A. media often confused. DNA barcoding combined with morphometric analyses has begun to clarify the distinction between these two morphologically similar species but has been limited in its geographic coverage to date. Herein, we provide DNA barcodes for 228 specimens collected from Guinea Bissau in the south, up the Atlantic coast, to the Irish shelf and North Sea. Employing species delimitation analyses, and with comparison to the literature, we identified 24 individuals of A. africana, 66 individuals of A. subulata and 138 individuals of A. media . We confirm that A. media has the northernmost distribution and is the only species identified by DNA sequencing from the Irish shelf and North Sea. We analysed morphometric measures and indices from 388 individuals from the North Sea, a subset of which ( n = 58) were barcoded. The most useful traits for identification were tail length as a percentage of dorsal mantle length, and largest club sucker width as a percentage of head width. By comparison to other published data, we determined that A. media phenotypes vary substantially across the geographic range of this species. This partly explains the difficulties in morphological identification and suggests regional identification guides may be required in support of fisheries management. Interregional analyses suggest character displacement may occur where species co-exist.

Cephalopods, a gap in the European Marine Strategy Framework Directive and their future integration - Bianca T. C. Bobowski; Anne Marie Power; Graham J. Pierce; Ana Moreno; Ane Iriondo; Julio Valeiras; Inna M. Sokolova; Daniel Oesterwind (Marine Biology, 2023)
With the aim of maintaining or obtaining good environmental status in the Northeast Atlantic and northern Mediterranean Sea, the European Marine Strategy Framework Directive (EU-MSFD) came into force in 2008. All EU Member States (MS) have the task of assessing the current state of their adjacent waters to guarantee sustainable use of marine resources and healthy ecosystems for the current and future generations. Although the MSFD has been implemented for over a decade, there are still gaps in the assessment of various ecologically and commercially important marine species, such as cephalopods. Here we describe the status of cephalopods, a key component of marine ecosystems and a valuable fishing resource, within the MSFD. To do so, we review how MS deal with this group in their reporting and identify and explain the gaps in the cephalopod assessment. We describe the main challenges including the limited data and the rarity of dedicated surveys on cephalopods. However, we argue that cephalopods can be partially integrated into the EU-MSFD assessment, illustrating the current opportunities and future possibilities of their integration into the MSFD, mainly using Descriptors 1–4. Graphical abstract

Climate change-related changes in cephalopod biodiversity on the North East Atlantic Shelf - Daniel Oesterwind; Christopher J. Barrett; Anne F. Sell; Ismael Núñez-Riboni; Matthias Kloppmann; Uwe Piatkowski; Kai Wieland; Vladimir Laptikhovsky (Biodiversity and Conservation, 2022)
Global studies imply that cephalopods have benefited from climate change. However, in most areas, species-specific long-term cephalopod data sets do not exist to support this implication and to analyse the response of cephalopods to environmental changes. Our results illustrate that historical studies, in combination with recent data sets, can fill this gap, enabling descriptions of ecological changes over a long time. We show substantial changes in the cephalopod biodiversity of the North Sea at species level over the past 100 years. Some species, which seemed to migrate into the North Sea only for spawning or foraging in the nineteenth century, occur permanently in the North Sea nowadays. This applies, for example, to the loliginids Loligo forbesii and Alloteuthis subulata. The ommastrephids Todaropsis eblanae and Illex coindetii, now constantly present as well, had been described only as accidental migrants 100 years ago.

Seasonal depth distribution and thermal experience of the non-indigenous round goby Neogobius melanostomus in the Baltic Sea: implications to key trophic relations - Jane W. Behrens; Marie P. Ryberg; Heli Einberg; Redik Eschbaum; Ann-Britt Florin; Wlodzimierz Grygiel; Jens Peter Herrmann; Bastian Huwer; Karin Hüssy; Elina Knospina; Kristiina Nõomaa; Daniel Oesterwind; et al. (Biological Invasions, 2022)
Native to the Ponto-Caspian region, the benthic round goby ( Neogobius melanostomus ) has invaded several European inland waterbodies as well as the North American Great Lakes and the Baltic Sea. The species is capable of reaching very high densities in the invaded ecosystems, with not only evidence for significant food-web effects on the native biota and habitats, but also negative implications to coastal fishers. Although generally considered a coastal species, it has been shown that round goby migrate to deeper areas of the Great Lakes and other inland lakes during the cold season. Such seasonal movements may create new spatio-temporal ecosystem consequences in invaded systems. To seek evidence for seasonal depth distribution in coastal marine habitats, we compiled all available catch data for round goby in the Baltic Sea since its invasion and until 2017. We furthermore related the depths at capture for each season with the ambient thermal environment. The round goby spend autumn and winter at significantly deeper and offshore areas compared to spring and summer months; few fish were captured at depths 25 m. The thermal conditions at which round goby were caught varied significantly between seasons, being on average 18.3 °C during summer, and dropping to a low 3.8 °C during winter months. Overall, the fish sought the depths within each season with the highest possible temperatures. The spatial distribution of the round goby substantially overlaps with that of its main and preferred prey (mussels) and with that of its competitor for food (flatfish), but only moderately with the coastal predatory fish (perch), indicating thereby very complex trophic interactions associated with this invasion. Further investigations should aim at quantifying the food web consequences and coupling effects between different habitats related to seasonal migrations of the round goby, both in terms of the species as a competitor, predator and prey.

Marine Protected Areas: At the Crossroads of Nature Conservation and Fisheries Management - Michael Kriegl; Xochitl E. Elías Ilosvay; Christian von Dorrien; Daniel Oesterwind (Frontiers in Marine Science, 2021)
Marine protected areas (MPAs) are designated parts of the ocean that restrict human activities to a certain degree. MPAs are established around the world using a wide range of legislative instruments and thus come in a variety of forms and shapes. Despite being regarded as the “cornerstone” of global marine conservation efforts, they currently cover less than 10% of the ocean surface. Individual MPAs aim to achieve goals ranging from the protection of specific habitats or species to sustaining certain commercial activities, such as fishing. By default, the establishment of MPAs intertwines social, ecological and economic considerations. Yet, the emphasis put on each of these domains can vary substantially when setting on-the-ground objectives, frequently creating conflict among stakeholders. In this manuscript, we first discuss current international conservation targets as well as potential future goals and delve into the question of how to assess the effectiveness of MPAs. Subsequently, we discuss the ambivalent role of this widely applied management tool at the crossroads between biodiversity conservation and fisheries management. Placing MPAs in a social-ecological framework, we call for clear and measurable goals to evaluate MPAs from an interdisciplinary perspective. Finally, we present the Baltic Sea, with its high degree of anthropogenic impact, long fishing history and comparatively extensive MPA coverage, as an interesting case study to investigate the role of MPAs in promoting a sustainable management of the ocean.

Habitat utilization and feeding ecology of small round goby in a shallow brackish lagoon - Christina Henseler; Paul Kotterba; Erik Bonsdorff; Marie C. Nordström; Daniel Oesterwind (Marine Biodiversity, 2020)
We examined small-scale distribution and feeding ecology of a non-native fish species, round goby ( Neogobius melanostomus (Pallas, 1814)), in different habitats of a coastal lagoon situated in the south-western Baltic Sea. First observations of round goby in this lagoon were reported in 2011, 3 years before the current study was conducted, and information on this species’ basic ecology in different habitats is limited. We found that mainly juvenile round gobies are non-randomly distributed between habitats and that abundances potentially correlate positively with vegetation density and thus structural complexity of the environment. Abundances were highest in shallower, more densely vegetated habitats indicating that these areas might act as a refuge for small round gobies by possibly offering decreased predation risk and better feeding resources. Round goby diet composition was distinct for several length classes suggesting an ontogenetic diet shift concerning crustacean prey taxa between small (≤ 50 mm total length, feeding mainly on zooplankton) and medium individuals (51–100 mm, feeding mainly on benthic crustaceans) and another diet shift of increasing molluscivory with increasing body size across all length classes. Differences in round goby diet between habitats within the smallest length class might potentially be related to prey availability in the environment, which would point to an opportunistic feeding strategy. Here, we offer new insights into the basic ecology of round goby in littoral habitats, providing a better understanding of the ecological role of this invasive species in its non-native range, which might help to assess potential consequences for native fauna and ecosystems.

First Evidence of Illex coindetii (Vérany, 1839) in the Baltic Sea and the Kattegat - Daniel Oesterwind; Matthias Schaber (Thalassas: An International Journal of Marine Sciences, 2020)

Electronic monitoring in fisheries: Lessons from global experiences and future opportunities - Aloysius T.M. van Helmond; Lars O. Mortensen; Kristian S. Plet‐Hansen; Clara Ulrich; Coby L. Needle; Daniel Oesterwind; Lotte Kindt‐Larsen; Thomas Catchpole; Stephen Mangi; Christopher Zimmermann; Hans Jakob Olesen; Nick Bailey; et al. (Fish and Fisheries, 2020)
Since the beginning of the 21st century, electronic monitoring (EM) has emerged as a cost‐efficient supplement to existing catch monitoring programmes in fisheries. An EM system consists of various activity sensors and cameras positioned on vessels to remotely record fishing activity and catches. The first objective of this review was to describe the state of play of EM in fisheries worldwide and to present the insights gained on this technology based on 100 EM trials and 12 fully implemented programmes. Despite its advantages, and its global use for monitoring, progresses in implementation in some important fishing regions are slow. Within this context, the second objective was to discuss more specifically the European experiences gained through 16 trials. Findings show that the three major benefits of EM were as follows: (a) cost‐efficiency, (b) the potential to provide more representative coverage of the fleet than any observer programme and (c) the enhanced registration of fishing activity and location. Electronic monitoring can incentivize better compliance and discard reduction, but the fishing managers and industry are often reluctant to its uptake. Improved understanding of the fisher's concerns, for example intrusion of privacy, liability and costs, and better exploration of EM benefits, for example increased traceability, sustainability claims and market access, may enhance implementation on a larger scale. In conclusion, EM as a monitoring tool embodies various solid strengths that are not diminished by its weaknesses. Electronic monitoring has the opportunity to be a powerful tool in the future monitoring of fisheries, particularly when integrated within existing monitoring programmes.

Predation of the round goby ( Neogobius melanostomus Pallas, 1814) on Atlantic herring eggs in the Western Baltic Sea - Joschka Wiegleb; Paul Kotterba; Cornelius Hammer; Daniel Oesterwind (Marine Biology Research, 2018)

Predation on Atlantic herring ( Clupea harengus ) eggs by the resident predator community in coastal transitional waters - Paul Kotterba; Dorothee Moll; Cornelius Hammer; Myron A. Peck; Daniel Oesterwind; Patrick Polte (Limnology and Oceanography, 2017)
Atlantic herring ( Clupea harengus ) migrates from offshore to coastal areas to spawn and their eggs and larvae may substantially increase prey resources for resident predators. We combined an in situ predator exclusion experiment using eggs naturally spawned on submerged aquatic vegetation and field observations of predator abundance to estimate the magnitude of predation mortality of herring eggs. During our predator exclusion experiment, performed in an important spawning ground in the southwest Baltic Sea, 20% of the herring eggs were consumed resulting in an extrapolated predation of 42% of all eggs between spawning and hatch. Abundance and stomach content analyses indicated that one predator (threespine stickleback, Gasterosteus aculeatus ) was responsible for the majority of the predation impact. Predation mortality estimates from this in situ study were more than 10‐fold higher than those of an empirical egg predation model for the same predator in the same region. Our findings highlight the potential of resident predators to regulate the survival of early life stages of ocean‐going fishes that rely on the nursery functions of inshore transitional waters.

Predator and prey: the role of the round goby Neogobius melanostomus in the western Baltic - Daniel Oesterwind; Christiane Bock; Anja Förster; Michael Gabel; Christina Henseler; Paul Kotterba; Marion Menge; Dennis Myts; Helmut M. Winkler (Marine Biology Research, 2017)

On distribution, size and maturity of shortfin squids (Cephalopoda, Ommastrephidae) in the North Sea - Daniel Oesterwind; Uwe Piatkowski; Heinz Brendelberger (Marine Biology Research, 2015)